Double-staining procedure for the fluorescent treponemal antibody absorption (FTA-ABS) test. - Hunter, E F (1979)
The fluorescent treponemal antibody absorption (FTA-ABS) double-staining procedure was reproducible, comparable to the conventional test, and easy to read. We recommend the use of the FTA-ABS double-staining procedure for microscopes with incident illumination, the 100 x/1.30 oil achromatic objective and the 6.3 x ocular to obtain optimal fluorescence, and the KP560 as a barrier filter to exclude rhodamine emission when fluorescein fluorescence is read. With this system, errors related to poor focusing or failure to visualise treponemes on all smears should be eliminated.